2020
DOI: 10.21203/rs.3.rs-25409/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Person-Centred Maternity Care in a Poor-Resource Setting: Evidence from a Cross-Sectional Study in Enugu State, Nigeria

Abstract: Background Women are not getting adequate person-centred maternity care (PCMC) in low-income and middle-income countries despite being important in reducing maternal morbidity and mortality. This study assessed perceptions and predictors of PCMC among childbearing women in Enugu State, South-east Nigeria.Methods The study was conducted in two health districts in Enugu State using a descriptive, cross-sectional survey design. We conveniently selected 450 childbearing women, within 9 weeks post-partum, from 11 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The least score was on the communication and autonomy sub-scale, while the highest was on the respect and dignity dimension. This result is consistent with studies done in India, and Nigeria which showed that the mean score of person-centered care during childbirth was 55.8, and 55.13 respectively [ 17 , 18 ]. The current finding showed that person-centered care during childbirth was low compared with the recommended scale value to say high person-centered care, which is above 75 percentile by the measurement tool validates and compared to other studies done in low- and middle-income countries [ 2 , 12 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The least score was on the communication and autonomy sub-scale, while the highest was on the respect and dignity dimension. This result is consistent with studies done in India, and Nigeria which showed that the mean score of person-centered care during childbirth was 55.8, and 55.13 respectively [ 17 , 18 ]. The current finding showed that person-centered care during childbirth was low compared with the recommended scale value to say high person-centered care, which is above 75 percentile by the measurement tool validates and compared to other studies done in low- and middle-income countries [ 2 , 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…Person-centered care during childbirth is measured using the PCC during childbirth scale, which has three domains: dignity and respect, communication and autonomy, supportive care, and 30 items with a four-point response scale. i.e., 0 “(“no, never””), 1 “(“yes, a few times””), 2 “(“yes, most of the time””),and 3 “(“yes all the time””) [ 5 , 6 , 16 ], and with negative items reverse coded so that high numbers represent good care). Therefore, the scale score ranges from zero to 90.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation